Ethnobotanical Study of Medicinal Plants in Bangbayang Village, Sumedang, West Java. - Riany, Adelia; Permatasari, Alissa Putri; Salsabila, Nazhifah; Nurlena, Nurlena; Rahayu, Sri Endarti; Marcelina, Meggie (Universitas Nasional Jakarta, 2024)
Ethnobotany can be defined as the study of the utilization of plants in a community, one of which is medicinal plants. The purpose of this research is to understand and identify the types of plants used in medicine and their processing methods by the community in Bangbayang Village, Sumedang, West Java. This study was conducted using qualitative and quantitative data analysis through five stages: observation, interviews, field observations, identification, and documentation. Based on interviews with 35 respondents, the diversity of medicinal plants obtained in the forest area of Bangbayang Village is 65 species from 38 families. These medicinal plants are utilized as traditional remedies, serving as alternatives and initial steps for treatment and care, which can be obtained directly from home gardens, community cultivation, or the forest. In this study, the most utilized plants as medicine belong to the Zingiberaceae family, with 6 species. The most commonly used plant parts are leaves, and the most common processing method is boiling. Using the Use Value (UV) calculation, Javanese tamarind, guava, and green betel show the highest UV values at 0.20. Meanwhile, in the calculation of Fidelity Level (FL), turmeric shows the highest FL value at 100%.